2020
DOI: 10.1080/01652176.2020.1712495
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, epidemiology, pathology, and advances in diagnosis, vaccine development, and treatment ofGallibacterium anatisinfection in poultry: a review

Abstract: Gallibacterium anatis is a Gram-negative bacterium of the Pasteurellaceae family that resides normally in the respiratory and reproductive tracts in poultry. It is a major cause of oophoritis, salpingitis, and peritonitis, decreases egg production and mortality in hens thereby severely affecting animal welfare and overall productivity by poultry industries across Europe, Asia, America, and Africa. In addition, it has the ability to infect wider host range including domesticated and free-ranging avian hosts as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 127 publications
(236 reference statements)
1
40
0
Order By: Relevance
“…Such monodominance of the gut microbiome by bacterial species has been described in diseased humans ( Hildebrand et al, 2019 ; Ravi et al, 2019 ), but is surprising in the context of poultry reported as apparently healthy by their handlers. We also noted a high relative abundance of the recently described chicken pathogen Gallibacterium anatis ( Narasinakuppe Krishnegowda et al, 2020 ) in most birds (with four birds showing >5% reads assigned to this organism), despite their healthy status. Similarly, Fusobacterium mortiferum —an opportunistic pathogen of humans ( Almohaya et al, 2020 )—accounted for >10% of sequences in 11 birds, corroborating a recent report of high abundance of 16S rRNA gene sequences from this organism obtained from the chicken caecum ( Kollarcikova et al, 2019 ).…”
Section: Resultsmentioning
confidence: 70%
“…Such monodominance of the gut microbiome by bacterial species has been described in diseased humans ( Hildebrand et al, 2019 ; Ravi et al, 2019 ), but is surprising in the context of poultry reported as apparently healthy by their handlers. We also noted a high relative abundance of the recently described chicken pathogen Gallibacterium anatis ( Narasinakuppe Krishnegowda et al, 2020 ) in most birds (with four birds showing >5% reads assigned to this organism), despite their healthy status. Similarly, Fusobacterium mortiferum —an opportunistic pathogen of humans ( Almohaya et al, 2020 )—accounted for >10% of sequences in 11 birds, corroborating a recent report of high abundance of 16S rRNA gene sequences from this organism obtained from the chicken caecum ( Kollarcikova et al, 2019 ).…”
Section: Resultsmentioning
confidence: 70%
“…Owing to the emergence of widespread multidrug resistance, traditional antimicrobial drugs are not indicated for this bacterial pathogen. The efficacy of classical vaccines in preventing this disease is limited due to disease antigenic diversity ( 32 ). Common G. anatis virulence factors include the capsule, outer membrane vesicles, fimbriae, metalloproteases, and biofilm formation, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Gallibacterium anatis is distributed globally as an important opportunistic pathogen in different poultry production systems [ 3 ]. The bacterium has been reported in several countries within Europe (Switzerland, Denmark, Germany, Norway, England, Sweden, Czech Republic, Austria), Africa (Nigeria, Egypt, Morocco), Asia (China, Taiwan, Iran, Syria, India and Japan) and American countries (USA, Canada, Colombia, Peru and Mexico) [ 3 ]. G. anatis is a Gram-negative, non-motile, encapsulated coccobacillus that constitutes part of the normal microbiota in the upper respiratory tracts and the lower genital tracts of healthy chickens [ 4 ].…”
Section: Introductionmentioning
confidence: 99%